2020
DOI: 10.1038/s12276-020-0382-4
|View full text |Cite
|
Sign up to set email alerts
|

A short guide to histone deacetylases including recent progress on class II enzymes

Abstract: The interaction between histones and DNA is important for eukaryotic gene expression. A loose interaction caused, for example, by the neutralization of a positive charge on the histone surface by acetylation, induces a less compact chromatin structure, resulting in feasible accessibility of RNA polymerase and increased gene expression. In contrast, the formation of a tight chromatin structure due to the deacetylation of histone lysine residues on the surface by histone deacetylases enforces the interaction bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
231
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 297 publications
(233 citation statements)
references
References 65 publications
(84 reference statements)
1
231
0
1
Order By: Relevance
“…A study by Feng and colleagues (48) demonstrated that application of histone deacetylase (HDAC) inhibitors was able to limit RSV replication in inoculated BEAS-2B cultures. The HDAC family of proteins are pleiotropic regulators of cellular function, which includes transcriptional repression, epigenetic modification, and signal transduction (133,150). Importantly, HDACs regulate microtubule disassembly and IFT processes in cilia and are critical in control of cilia length (58,149,213).…”
Section: Respiratory Syncytial Virusmentioning
confidence: 99%
“…A study by Feng and colleagues (48) demonstrated that application of histone deacetylase (HDAC) inhibitors was able to limit RSV replication in inoculated BEAS-2B cultures. The HDAC family of proteins are pleiotropic regulators of cellular function, which includes transcriptional repression, epigenetic modification, and signal transduction (133,150). Importantly, HDACs regulate microtubule disassembly and IFT processes in cilia and are critical in control of cilia length (58,149,213).…”
Section: Respiratory Syncytial Virusmentioning
confidence: 99%
“…Class IV is represented by HDAC11 (Haberland et al, 2009). HDACs class I, II and IV require Zinc-dependent catalysis as cofactors for their enzymatic activity and HDACs class III or Sirtuins required nicotinamide adenine dinucleotide (NAD)-dependent (Park and Kim, 2020).…”
Section: Histone Deacetylases: An Overviewmentioning
confidence: 99%
“…The acetylation of p53 can be reversed by various histone deacetylases (HDACs). In humans, there are four classes of HDAC (Class I, Class IIa/b, Class III and Class IV) 76 . These classes can be divided into two families based on the conserved deacetylase domain and their specific cofactors: the HDAC family (Class I and Class IIa/b) and the sirtuin protein family (Class III and Class IV) 76 .…”
Section: -3-3 Regulation Of P53 Acetylationmentioning
confidence: 99%
“…In humans, there are four classes of HDAC (Class I, Class IIa/b, Class III and Class IV) 76 . These classes can be divided into two families based on the conserved deacetylase domain and their specific cofactors: the HDAC family (Class I and Class IIa/b) and the sirtuin protein family (Class III and Class IV) 76 . HDAC 1 (Class I) is one of the most prominent deacetylase enzymes for p53 and it represses p53-dependent transcriptional activation, cell cycle arrest and apoptosis 77 .…”
Section: -3-3 Regulation Of P53 Acetylationmentioning
confidence: 99%